Strength and Deformability of Fiber Reinforced Cement Paste on the Basis of Basalt Fiber - Yury Barabanshchikov; Ilya Gutskalov (Advances in Civil Engineering)
The research object of the paper is cement paste with the particulate reinforcement of basalt fiber. Regardless of fibers’ length at the same fiber cement mix workability and cement consumption equality compressive solidity of the specimens is reduced with increasing fiber content. This is due to the necessity to increase the water-cement ratio to obtain a given workability. The flexural stability of the specimens with increasing fiber content increments in the same conditions. There is an optimum value of the fibers’ dosage. That is why stability has a maximum when crooking. The basaltic fiber particulate reinforcement usage can abruptly increase the cement paste level limiting extensibility, which is extremely important in terms of crack resistance.